EFFECTS OF LUDARTIN AND LEUKOMISIN ON THE ACUTE HYPERLIPIDEMIA MODEL INDUCED BY ETHANOL - A. V. Ratkin; O. A. Kaidash; V. V. Ivanov; A. I. Vengerovsky; S. M. Adekenov; V. S. Chuchalin (Бюллетень сибирской медицины)
Objective: study sesquiterpene lactones ludartin and leukomisin lipid-lowering properties on the model of acute hyperlipidemia induced by ethanol in rats.Material and methods. Rats during 7 days injected into the stomach ludartin and leukomisin in a dose 10 mg/kg or reference drug nicotinic acid in a dose 25 mg/kg. Hyperlipidemia caused by single introduc-tion of ethanol into the stomach in a dose 5 g/kg. In blood serum of tail vein measured the triacylgly-cerols, total cholesterol, high density and low density lipoproteins cholesterol, also the level of free fatty acids. Calculated the ratio of high density lipoproteins cholesterol to the amount of low density lipopro-teins cholesterol and the index of atherogenicity.Results. A single dose of ethanol increased serum level of triacylglycerols in 1.9 times, free fatty acids – in 3.2 times, low density lipoproteins – on 44% in comparison with the intact animals indices. It shows the development of acute hyperlipidemia. Serum total cholesterol, high density lipoproteins cholesterol and the index of atherogenicity were not changed. Course introduction of sesquiterpene lactones ludartin and leukomisin against the background of acute hyperlipidemia was accompanied by a decrease in the serum of triacylglycerols levels respectively by 37.5% and 49.5%. Nicotinic acid lowered the content of triacylglycerols by 42.4%. Ludartin, leukomisin and nicotinic acid reduced the increased level of free fatty acids in the blood serum by 63.4%, 41.6% and 67.9%. Ludartin, leukomisin and nicotinic acid de-creased by 15.8%, 20.3% and 17.2% of total cholesterol in the blood serum. In acute hyperlipidemia ludartin and leukomisin reduced low density lipoproteins cholesterol by 23.8% and 14.8%, respectively, nicotinic acid – by 15.7%. Both of sesquiterpene lactone and nicotinic acid did not modify the content of high density lipoproteins cholesterol. When introduction ludartin and nicotinic acid ratio of high density lipoproteins cholesterol to the amount of low density lipoproteins cholesterol significantly increased by 32.7% and 22.1% respectively.Conclusion. Sesquiterpene lactones ludartin and leukomisin posses hypolipidemic effect in acute experi-mental hyperlipidemia caused by the ethanol introduction. Lactones normalize many indices of lipid me-tabolism, which can be caused by different biochemical targets of these molecules. Lactones, as nicotinic acid, in the model of acute hyperlipidemia decrease in blood serum triacylglycerols, total cholesterol, and low density lipoproteins cholesterol content.